2001
DOI: 10.14742/ajet.1769
|View full text |Cite
|
Sign up to set email alerts
|

Can multimedia meet tertiary educational needs better than the conventional lecture? A case study

Abstract: Educational researchers have long derided the university lecture as an effective mode of delivery of educational materials, but currently there are many reports on the advantages offered by computer. In this study a multimedia solution was sought to replace existing face to face lectures because it appeared to offer a close 'media versus need' match. Consequently, a decision was made to develop a design template for an interactive computer based program that would be suitable for a range of subject content. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…There is a growing body of literature on the use of web based discussions as a lever for building socially constructed student centred learning (Andrewartha & Wilmot, 2001;Beerman, 1996;Brennan, McFadden & Law, 2001;Dunlop & Scott, 2001;Halsne & Gatta, 2002;Jacobs, 2003;Kim & Bonk, 2006;McLoughlin, 2000;Mioduser, Nachmias, Lahav & Oren, 2000;O'Grady, 2001;Ramsay, 2005;Watrall & Ellison, 2006). Computer based communication is an effective way to increase both social connectivity between learners and collaborative exploration of ideas (Graham & Scarborough, 1999).…”
Section: Information and Communications Technology: Bloggingmentioning
confidence: 99%
“…There is a growing body of literature on the use of web based discussions as a lever for building socially constructed student centred learning (Andrewartha & Wilmot, 2001;Beerman, 1996;Brennan, McFadden & Law, 2001;Dunlop & Scott, 2001;Halsne & Gatta, 2002;Jacobs, 2003;Kim & Bonk, 2006;McLoughlin, 2000;Mioduser, Nachmias, Lahav & Oren, 2000;O'Grady, 2001;Ramsay, 2005;Watrall & Ellison, 2006). Computer based communication is an effective way to increase both social connectivity between learners and collaborative exploration of ideas (Graham & Scarborough, 1999).…”
Section: Information and Communications Technology: Bloggingmentioning
confidence: 99%
“…Their writing becomes a response to discussion that will stimulate further discussion. The creation of "responsive and active learning environments" (Cicognani, 2000;Hannafin & Hill, 2002, p.77) leads to an improvement of learning effectiveness of this group of students since online collaboration pedagogy utilizes peer help in constructing knowledge (Xun, Yamashiro & Lee, 2000;Andrewartha & Wilmot, 2001). …”
Section: Enhancing Interactivitymentioning
confidence: 99%
“…For investigating the effect of e-learning in post-test on participants' test anxiety, achievement motivation and academic achievement with regard to the research conditions, 1 Educational planning method that was introduces by Sebastian Leitner (Jones, 2010). In this method questions were planned in 5 boxes and student has to study the questions and move them from first box in to other four boxes in terms of right or wrong answers.…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that using technology instruments can clearly increase students' cognitive outcomes. Andrewartha and Wilmot (2001) also have studied the use of multimedia to argue the studants' learning as a strategy for enhancing active learning among students. In this study they developed a multimedia course on 'editing' to replace traditional classroom based teaching on editing subject.…”
Section: Introductionmentioning
confidence: 99%